Transposon-triggered epigenetic chromatin dynamics modulate EFR-related pathogen response - Mencia, Regina (2024)
Infectious diseases drive wild plant evolution and impact crop yield. Plants, like animals, sense biotic threats through pattern recognition receptors (PRRs). Overly robust immune responses can harm plants; thus, understanding the tuning of defense response mechanisms is crucial for developing pathogen-resistant crops. In this study, we found that an inverted-repeat transposon (EFR-associated IR, Ea-IR) located between the loci encoding PRRs ELONGATION FACTOR-TU RECEPTOR (EFR) and myosin XI-k (XI-k) in Arabidopsis affects chromatin organization, promoting the formation of a repressive chromatin loop. Upon pathogen infection, chromatin changes around EFR and XI-k correlate with increased EFR transcription. Pathogen-induced chromatin opening causes RNA polymerase II readthrough, producing a longer, Ea-IR-containing XI-k transcript, processed by Dicer-like enzymes into small RNAs, which reset chromatin to a repressive state attenuating the immune response after infection. Arabidopsis accessions lacking Ea-IR have higher basal EFR levels and resistance to pathogens. We show a scenario in which a transposon, chromatin organization and gene expression interact to fine-tune immune responses, during both the course of infection and the course of evolution.